If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + 2x = 4x + -6 Reorder the terms: -8 + 2x = -6 + 4x Solving -8 + 2x = -6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -8 + 2x + -4x = -6 + 4x + -4x Combine like terms: 2x + -4x = -2x -8 + -2x = -6 + 4x + -4x Combine like terms: 4x + -4x = 0 -8 + -2x = -6 + 0 -8 + -2x = -6 Add '8' to each side of the equation. -8 + 8 + -2x = -6 + 8 Combine like terms: -8 + 8 = 0 0 + -2x = -6 + 8 -2x = -6 + 8 Combine like terms: -6 + 8 = 2 -2x = 2 Divide each side by '-2'. x = -1 Simplifying x = -1
| 2x-95=x+4 | | 6x+8-x=-47 | | 3=5(x-4)+1-4x | | -4x-x=11(4x-11)+4(4-11x) | | 3=5(x-4)*1-4x | | 6m+3n+4m+8n= | | y=x^2-6x+k | | f(x+4)=x^2+2x-8 | | 5-3y+y= | | 65-13.5(0.2P-1.5)=7.5 | | 0.05P+0.07(1200-P)=80 | | 11(1-9x)=-7-12(5x-8) | | -5x+4y= | | 3/6-2/15 | | 152.34=2.95h+72.69 | | 4(3x+1)=5x-8x | | 7x^3e^7x-3x^2e^7x/x^6 | | 11(1+2p)+8(1-7p)=-7p-8p | | (6x^4)-(24x^2)=0 | | x/2=x/3=-10 | | x-1=-3+x | | -2-3n=-2(1+4n) | | q-10whenq=13 | | 2y^2-y=28 | | 10y=2x-15 | | 161/14 | | -8a-5=163 | | 14/161 | | x2-2=-7x/4 | | tan(2x)=tan(x+30) | | 3+12=-5(9x-3) | | 3(x+12)+8x=11x-36 |